Identification Of Tourist Area Life Cycle In Gebong Memarong Tourist Village, Bangka Regency - Lestari, Zakia Ayu; Marmaiyatno, Marmaiyatno; Pusparini, Marissa; Marwani, Iga Safa; Prima, Anugrah Gusta (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Air Abik Hamlet, Gunung Muda Village, Belinyu Subdistrict, Bangka Regency, is a settlement of the oldest tribe in the Bangka Belitung Islands, the Lom Tribe. Famous for its magical village, but also has the potential for very beautiful natural tourism and local wisdom that is still maintained to this day. It has successfully collaborated with one of the BUMNs in Bangka and in 2023 it will become one of the tourist villages. Aik Abik Hamlet has enormous and interesting potential, but until now it has not been well identified. The research used descriptive qualitative methods and the research data was conducted by direct interviews with the head of the mapur customary institution, literature review and combined with primary data searches. The results of the research concluded that Gunung Muda Tourism Village is at the stage of involvement. Afterward, several things that need to be considered by stakeholders are improving tourist facilities such as tourist trails offered, promoting tourism through various media, and increasing local community involvement. In planning the future development of tourist destinations, visitor capacity needs to be considered so that existing facilities can be maintained and do not have a negative impact on the environment. The community is expected to continue to improve their knowledge and insight so that they can support progress in Gunung Muda Tourism Village.